Analytical Solutions for Steady-State Multiwell Aquifer Tests in Rectangular Aquifers by Using Double Fourier Transform: A Case Study in the Ordos Plateau, China. (26th February 2020) - Wang, Jun-Zhi; Wang, Xu-Sheng; Li, Qing-Bo; Wan, Wei-Feng
Abstract : Straightforward solutions have long been expected for the analysis of multiwell aquifer tests. In this paper, we derive series analytical solutions of steady-state groundwater flow in a rectangular-shaped aquifer with pumping/injection wells for both confined and unconfined conditions. Double Fourier Transform (DFT) technique is applied to deal with different combinations of impermeable and specified head boundaries on sides. The obtained solutions are compact and concise in mathematics and flexible in terms of well number, well locations, and pumping/injection rates. Hatoucaidang, a groundwater resource field in the Ordos Plateau, Northwestern China, is introduced as a field case study, where a multiwell aquifer test was conducted. One of the analytical solutions derived herein is used to estimate hydraulic conductivities by applying a direct calculation method and a least square estimation method regarding observed versus calculated drawdowns. By comparing with nearby single-well pumping tests, the reliability of the derived analytical solutions is proven. This study facilitates utilizing the multiwell aquifer test to analyze the general behavior of groundwater movement in aquifer systems.